The stylistic shift in diwan/poetical work (Al-Kademon Al-Kodor) - Mehzri, Nouf Yahya; Al-Ghamdi, Hanan Abdullah (Journal of Arabic Language Sciences and Literature, 2023)
This article aims to study the poetry of Salim Abdel Al-Qader (Al-Kademon Al-Kodor) in a stylistic manner through the shift theme, which expresses the change of speech from its ideal format for rhetorical purposes and benefits. The study was divided into a preface and three chapters; we dealt with conceptual approaches in the preface, then presented the rhythmic shift in the first chapter, the syntactic in the second chapter, and the semantic in the third chapter, according to a descriptive and analytical approach to poetic styles. We concluded that Abdul Al-Qadir resorted to multiple forms of shifts that revealed the features of his poetry, its richness as a stylistic feature full of connotations, and the poet's tendency to imitate the ancients. Therefore, we recommend in the study tracing the poet's skill to reveal the psychological influences that refined his experience, and we draw attention to studying his poetry from the perspective of prison literature, considering it a prominent feature in his poetic experience.
Keywords: Salim Abdel Al-Qader; shift; rhythm; poetic meters